'Translanguaging' a harbinger of language and cultural loss in Africa? The central role of schools in the transmission of standard forms of African languages. - (:unkn) unknown (My University, 2013)
In the present situation where oral formal learning practices in Africa tend to dwindle drastically, schools have become one central resource for the transmission of the more classical forms of African languages. At least for the languages which can boast a literate tradition, space can be easily carved out in curricula. The fashionable tendency to accept any new (African) language form as exhibited by the hype around 'Translanguaging' should not result in sanctioning language and cultural loss. Creolization and pidginization may not be the desired end of all African languages.
Keywords: African Research